Pengaruh Manajemen Kelas dan Disiplin Belajar terhadap Hasil Belajar Matematika Siswa - Sukmawati, Sukmawati; Adam, Adam; Bagea, Ishak (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2025)
Mathematics learning outcomes in Indonesian junior high schools, particularly in rural areas such as Pakue Tengah District, North Kolaka, remain below expectations. Many students fail to reach the Minimum Completion Criteria (KKM), indicating the need to examine classroom-level factors that may influence achievement. This study aims to analyze the relationship between classroom management and learning discipline with students’ mathematics learning outcomes. A survey method with a correlational approach was employed, involving a sample of 73 eighth-grade students selected using stratified random sampling. Data were collected through questionnaires on classroom management and learning discipline, along with mathematics achievement tests, and analyzed using multiple linear regression. The results show that classroom management has a positive and significant relationship with mathematics outcomes (r = 0.579; R² = 33.52%), while learning discipline also demonstrates a significant relationship (r = 0.533; R² = 28.41%). Together, both variables explain 55.95% of the variance in students’ mathematics achievement. These findings align with prior studies highlighting the importance of effective classroom management and discipline in enhancing student engagement and learning results. The study implies that teachers should strengthen classroom management strategies, promote learning discipline, and foster conducive environments. Academically, the research contributes by providing empirical evidence from a rural Indonesian context, while practically it offers recommendations for teacher training and school policy to improve mathematics achievement.